Exploitation of Freedom, Relocating Chinese Coolies in the 1860s' U.S. - Wang, Haitao. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of History.; Advisors: Reed Ueda, and Ayesha Jalal.; Committee: Reed Ueda, Ayesha Jalal, and Deborah Schildkraut.; Keywords: History, Asian American studies, and American history.